Estudo e ensaio de um motor de indução monofásico para a determinação do valor ótimo do capacitor de regime - Fernandes, Hugo Knippelberg Bifano [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work focus on the Single Phase Induction Motors used in fans, classified as CapacitorRun Motors, using permanently series capacitors connected to the auxiliary winding and these parallel connected to the main winding. This motor works similarly to a Two-Phase Asymmetrical motor. This work aims to evaluate the influence of the used capacitance value on the energy efficiency of the capacitor-run motor. In order to reach this purpose it was used as an objective function to be maximized, the ratio between the speed (rpm) and the power consumed by the motor (W) during its permanent regime running. The choice of this objective function is pertinent since the majority of fans do not require a high starting torque and power. In this work, several tests were performed with a ceiling fan, the only change made for each test was the value of the used capacitor (or association of capacitors) in the motor. A simulation of a single-phase induction motor was carried out through SIMULINK, in this simulation the capacitance of the capacitor increased linearly with the simulation time, thus enabling the evaluation of the influence of this capacitor in real time. In the tests, a 12% improvement in the objective function was obtained with the optimum capacitor in relation to the result where the fan's nominal capacitor was used. The simulation showed an increase in 11% in the objective function when comparing the result obtained with the optimum capacitor to that one obtained with the nominal capacitor. It was concluded that the method used in the work is valid in cases in which the main objective is a gain in energy efficiency, since the suggested change has as a counterpart a small reduction in the speed reached by the fan.
Study and test of a single phase induction motor for determination of the optimum value of the regeneration capacitor
Keywords: Motores elétricos de indução; Maquinas eletricas; Energia elétrica - Consumo; Capacitadores; Electric power consumption